Evaluation of Teaching Speaking Skills Based on Interpersonal Intelligence - Octriana, Leny (JURNAL IJ-ATL, 2023)
Teaching speaking skills in secondary education requires approaches that not only enhance verbal fluency but also align with students' social and emotional development. This study aims to evaluate the implementation of interpersonal intelligence-based strategies in teaching speaking skills and their effectiveness in improving students' oral communication competence. The background of this research stems from the need to develop speaking instruction methods that are interactive, student-centered, and responsive to individual communication styles. By emphasizing interpersonal intelligence, such as empathy, collaboration, and effective peer interaction, teachers are expected to foster a more engaging and emotionally supportive learning environment. This research employs a qualitative descriptive approach, collecting data through classroom observations, in-depth interviews with English teachers and students, and documentation of speaking activities. The findings reveal that the use of interpersonal strategies like role-playing, group discussions, and peer feedback significantly increases student participation, confidence, and speaking fluency. In practice, these strategies also reduce students’ anxiety and promote a stronger sense of connection within the classroom. The implications of this study suggest that integrating interpersonal intelligence in teaching speaking can serve as a powerful pedagogical foundation to support holistic communication skills development in secondary education.